Some Dibenzyltellurium(IV) Complexes with Schiff Base Ligands : A photoelectron Spectroscopic Study - Srivastava, Shekhar; Singh, Deepa (Asian Journal of Chemistry, 2010)
Three complexes of Te(IV) of the type [R2TeSB] (where R = C6H5CH2, SB = Schiff base ligands, i.e., acac2en = bis- (acetylacetone)-ethylenediamine, benac2en = bis-(benzoylacetone)- ethylenediamine and dibenmethan2en = bis-(dibenzoylmethane)-ethylenediamine) have been prepared and their structures have been assigned on the basis of elemental analysis, molar conductance, IR and X-ray photoelectron spectral data.